Comparative Evaluation of Occlusion with and Without Finishing and Detailing Post Orthodontic Treatment Using T-Scan: A Prospective Follow-Up Study - Anwesha Chattopadhyay; Tejashri Pradhan; Aditya Acharya (Journal of Orofacial Sciences)
Introduction: The phases of orthodontic treatment include Initial Leveling and aligning, space closure, finishing detailing, settling, and retention. The phase of finishing and detailing in orthodontic treatment has a crucial role in refining the occlusion and ensuring long-term stability. However, the effectiveness of orthodontic treatment is not solely assessed by the alignment of teeth and jaws but also by achieving stable occlusion posttreatment. Hence, the study aims to evaluate postorthodontic occlusion in patients who meet the set criteria of finishing and detailing compared to those who have not, using a digital occlusal analyzer. Materials and methods: The posttreatment records of 42 patients who had undergone debonding after fixed mechanotherapy were evaluated for categorizing the patients based on the inclusion criteria into Groups A and B. The occlusal parameters of the patients were evaluated at time intervals—T1 (30 min after debonding), T2 (3 months after debonding), and T3 (6 months after debonding). The occlusal parameters evaluated were—force distribution in the right and left sides and anterior–posterior force %. Results: In a comparative evaluation between Groups A and B, it was seen that occlusion time, force distribution between the right and left sides, and the anteroposterior force distribution in the anterior and the posterior aspect were higher in Group B as compared to A. Conclusion: The results of our study indicated that in patients who had met the goals of finishing and detailing, the occlusal parameters showed near-ideal values as compared to the patients who had not met the goals of finishing and detailing. Digital analysis obtained using T-Scan is essential during the process of finishing and detailing to obtain a stable and well-balanced occlusion by the end of the orthodontic treatment.